2020
DOI: 10.1589/jpts.32.584
|View full text |Cite
|
Sign up to set email alerts
|

Principal motion analysis of manual stretching techniques for the ankle joints

Abstract: [Purpose] Physical therapists frequently perform manual stretching of the ankle joints. Manual stretching procedures are challenging to define because they involve multidirectional joint motions and external forces. Therefore, in this paper, we propose a method for quantitatively and statistically analyzing the manual foot stretching techniques used by physical therapists. [Participants and Methods] The participants were four physical therapists, and three patients who have a spastic foot. We investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Their machine had one degree of freedom of motion for dorsi- and plantar flexion. On the other hand, Yamada et al investigated physical therapists’ manual stretching techniques and statistically revealed that the therapist stretched the foot in three dimensions 16 , 17 ) . Their research group subsequently developed a three-dimensional control foot-stretching device that simulates this manual stretching technique 18 , 19 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Their machine had one degree of freedom of motion for dorsi- and plantar flexion. On the other hand, Yamada et al investigated physical therapists’ manual stretching techniques and statistically revealed that the therapist stretched the foot in three dimensions 16 , 17 ) . Their research group subsequently developed a three-dimensional control foot-stretching device that simulates this manual stretching technique 18 , 19 ) .…”
Section: Introductionmentioning
confidence: 99%